The Role of Context in clarifying of Ibn Badis Political Purposes –The Issue of Integration as a Model - Zakar, BELKACEM; Boudrama, ELZAIDI (Milev Journal of Research and Studies, 2022)
. This research confirms the role of context (both types) in clarifying rhetorical purposes. It indicates that the intentions may not be expressed, but may be implicit and expressed in an indirect way, thus needing mechanisms to reveal them, so the aim of this research is to invest the mechanism of context (both of them) in analyzing texts and interrogating their implications. We have taken from some of Ibn Badis' political speeches opposing the idea of ​​integration models and samples for application, analysis and projection. The research concluded, after investing the context mechanism in reading Badisian political discourses, a new reading to clarify the true position of Ibn Badis, rejecting this colonial policy.